Fenomena Nikah Siri Di Samarinda Dalam Perspektif Maslahah Al-Mursalah: Kajian Yuridis-Empiris - Mujennih; Aldi Pebrian (Science and Education Journal (SICEDU), 2026)
The practice of unregistered marriage in Samarinda City remains a significant social phenomenon despite state regulations requiring marriage registration. This study aims to analyze the factors causing the prevalence of unregistered marriage in Samarinda and examine it through the perspective of Maslahah al-Mursalah. Using a qualitative method with a juridical-empirical approach, data were collected through a literature review. The results indicate that economic factors, administrative barriers for migrant residents, and the role of unofficial marriage registrars are the main drivers in the Samarinda region. From the perspective of Maslahah al-Mursalah, marriage registration is an important instrument to protect the dharuriyat (primary) rights of wives and children. The practice of unregistered marriage is considered to contain mafsadat (damage) that outweighs its benefits, making administrative marriage registration a sharia obligation to achieve legal justice and social protection